Deiksis Persona dalam Al-Qur’an surat Al-Waqi’ah - Tajuddin Ahmad (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
Language is the most important suggestion in communicating. Language also has its scientific value, one of the studies in linguistics or linguistics is pragmatics. In the discussion of pragmatics there is a study of deixis where a word has a meaning to refer to the meaning of something before. Deixis is a phenomenon of tagging contextual information by using lexical forms or grammatical distinctions whose information will only become clear when related to the context. Phenomena involving sentence expressions that cannot be separated from the context are referred to as deictic expressions. Meanwhile, some linguistic forms used to show something are called deitic. The Qur'an is a book that contains very deep meanings and is even progressive to study. If seen from the study of semantics, the Koran contains words that are full of meaning. On this occasion the researcher will conduct his study on Surah Al Waqi'ah and focus on the study of Persona Deixis